An analytical investigation of hydroxylated cinnamoyl polyamines as biomarkers of commercial bee pollen botanical origin. (27th October 2022) - Nasti, Rita; Orlandini, Serena; Furlanetto, Sandra; Casale, Monica; Daci, Armond; Hajdari, Avni; Meneghetti, Fiorella; Villa, Stefania; Mori, Matteo; Beretta, Giangiacomo
Summary: In this study, the phytochemical profile of commercial pollen samples was investigated using different analytical approaches. The samples pollen composition was monitored by optical microscopy. The infrared spectrum of the ethanol extractable material form different pollen samples indicated the specific presence of an aromatic portion in samples dominated by pollens from arboreal species of sweet chestnut pollen grains ( e.g. Castanea sativa Mill. and Prunus ). In addition, the UPLC‐PDA analysis showed the ubiquitarian presence of an array of different derivatives confirmed as hydroxylated cinnamoyl derivatives of spermidine (major) and of spermine (minor). This profile appeared to be associated with the sample botanical origin. Samples dominated by chestnut honey pollen grains showed the highest content in total amount of these derivatives, with a peculiar profile dominated by the presence of N 1, N 5, N 10 ‐tricaffeoyl spermidine. The results showed that their average chemical composition is quantitatively and qualitatively correlated to their botanical origin, suggesting the feasibility of this approach as a practical tool to monitor plant population using honeybee pollen as a bioindicator of the impact of natural and anthropic processes at the local and global level. Abstract : Pollen is a known source of interesting chemical derivatives, among which spermidine/spermine‐containing hydroxylated cinnamoyl polyamines. Instrumental analytical methodologies may prove useful to discriminate the main botanical origin of commercial bee pollen.